STRUKTUR NARASI NOVEL SEJARAH ISLAM 17 RAMADAN - Moh. Wakhid Hidayat (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
17 Ramadan is a historical islamic novel by Jurji Zaidan. This is the fourth of his twenty-three historical novel. 17 Ramadan is originally published by al-Hilal newspaper. This novel tells about the events before and after the murder of Caliph Ali ibn Abi Talib on 17 Ramadan. This article presents the narrative structure of the novel with a structural analysis of Greimas’ narrative theory. This research aims to identify the structural action with binary opposition; the sender-recipient, subject and object, and the adjuvant-obstacle. The result finds that there are four main actantial structures. These structures construct five macrostructures, those are the linear structure of revenge-action-judgement, the structure of the characters’ vindication, the linear structure of insult-thesanity-and-holy-place-chastisement, the structure with isotope of place clarification, and the structure of heroine.